CRM1 Inhibitors for Antiviral Therapy - Mathew, Cynthia; Ghildyal, Reena (Frontiers in Microbiology, 2017)
Infectious diseases are a major global concern and despite major advancements in medical research, still cause significant morbidity and mortality. Progress in antiviral therapy is particularly hindered by appearance of mutants capable of overcoming the effects of drugs targeting viral components. Alternatively, development of drugs targeting host proteins essential for completion of viral lifecycle holds potential as a viable strategy for antiviral therapy. Nucleocytoplasmic trafficking pathways in particular are involved in several pathological conditions including cancer and viral infections, where hijacking or alteration of function of key transporter proteins such as CRM1 is observed. Overexpression of CRM1-mediated nuclear export is evident in several solid and hematological malignancies. Interestingly, CRM1-mediated nuclear export of viral components is crucial in various stages of the viral lifecycle and assembly. This review summarizes the role of CRM1 in cancer and selected viruses. Leptomycin B is the prototypical inhibitor of CRM1 potent against various cancer cell lines overexpressing CRM1 and in limiting viral infections at nanomolar concentrations in vitro. However, the irreversible shutdown of nuclear export results in high cytotoxicity and limited efficacy in vivo. This has prompted search for synthetic and natural CRM1 inhibitors that can potentially be developed as broadly active antivirals, some of which are summarized in this review.